Previous Experience Seems Crucial to Eliminate the Sex Gap in Geometry Learning When Solving a Navigation Task in Rats (Rattus norvegicus) - Aguilar-Latorre, Alejandra; Romera-Nicolás, Víctor; Gimeno, Elisabet; Chamizo, V. D. (Frontiers in Psychology, 2022)
There is much evidence, both in humans and rodents, that while navigating males tend to use geometric information whereas females rely more on landmarks. The present work attempts to alter the geometry bias in female rats. In Experiment 1 three groups of female rats were trained in a triangular-shaped pool to find a hidden platform, whose location was defined in terms of two sources of information, a landmark outside the pool and a particular corner of the pool. On a subsequent test trial with the triangular pool and no landmark, females with prior experience with two other pool shapes ─with a kite-shaped pool and with a rectangular-shaped pool (Group Long Previous experience, LPE), were significantly more accurate than control rats without such prior experience (Group No Previous experience, NPE). Rats with a short previous experience ─with the rectangular-shaped pool only (Group Short Previous experience, SPE) did not differ from Group NPE. These results suggest that the previous experience with different shaped-pools could counteract the prominence of the landmark cue in female rats. Then, Experiment 2A directly compared the performance of LPE males and females of Experiment 1, although conducting several test trials (i.e., shape, landmark, and preference). The differences between males and females disappeared in the three tests. Moreover, in a final test trial both males and females could identify the correct corner in an incomplete pool by its local, instead of global, properties. Finally, Experiment 2B compared the performance of NPE rats, males and females, of Experiment 1. On the test trial with the triangular pool and no landmark, males were significantly more accurate than females. The results are explained in the framework of selective attention.